Effects of sample preservation and DNA extraction on enumeration of antibiotic resistance genes in wastewater. Issue 2 (27th December 2017) - Li, An-Dong; Metch, Jacob W; Wang, Yulin; Garner, Emily; Zhang, An Ni; Riquelme, Maria V; Vikesland, Peter J; Pruden, Amy; Zhang, Tong
Abstract: With the growing application of high-throughput sequencing-based metagenomics for profiling antibiotic resistance genes (ARGs) in wastewater treatment plants (WWTPs), comparison of sample pretreatment and DNA extraction methods are needed to move toward standardized comparisons among laboratories. Three widely employed DNA extraction methods (FastDNA ® Spin Kit for Soil, PowerSoil ® DNA Isolation Kit and ZR Fecal DNA MiniPrep), with and without preservation in 50% ethanol and freezing, were applied to the influent, activated sludge and effluent of two WWTPs, in Hong Kong and in the USA. Annotated sequences obtained from the DNA extracted using the three kits shared similar taxonomy and ARG profiles. Overall, it was found that the DNA yield and purity, and diversity of ARGs captured were all highest when applying the FastDNA SPIN Kit for Soil for all three WWTP sample types investigated here (influent, activated sludge, effluent). Quantitative polymerase chain reaction of 16S rRNA genes confirmed the same trend as DNA extraction yields and similar recovery of a representative Gram-negative bacterium ( Escherichia coli ). Moreover, sample fixation in ethanol, deep-freezing and overseas shipment had no discernable effect on ARG profiles, as compared to fresh samples. This approach serves to inform future efforts toward global comparisons of ARG distributions in WWTPs. Abstract : This approach moves toward standardized comparisons of ARG profiles among laboratories and serves to inform future efforts toward global comparisons of ARG distributions in WWTPs.